A Situational Analysis of Landlessness among the Santhal People in Morang District - Prasai, Dilli R. (BARUN Journal, 2026)
This study examines the situation of landlessness among the Santhal community in Ward No. 2 of Rangeli Municipality, Morang District. Despite being an indigenous national group, the Santhal people continue to face systemic exclusion from land ownership in an agrarian society where land determines livelihood, dignity, and social inclusion. The research is guided by two key questions: (1) What are the underlying causes and current patterns of landlessness among the Santhal community in the study area? (2) How does landlessness affect their socio-economic conditions, rights, and access to basic services? Accordingly, the objectives are to examine the structural and historical causes of landlessness and to analyse its socio-economic impacts on the community. The study adopts a mixed-method case study approach, combining descriptive and exploratory designs. Primary data were collected through household surveys (63 respondents), two focus group discussions, and two case studies, while secondary data were obtained from government reports, academic literature, and NGO publications. The findings reveal that nearly 73% of respondents live on public (Ailani) land without secure tenure, and many depend on Adhiya (sharecropping) farming and daily wage labour. Major causes of landlessness include historical land dispossession, lack of education and legal awareness, poverty, weak documentation, and ethnic marginalization. The impacts are severe, including insecure housing, limited access to services, restricted educational opportunities, and exclusion from government schemes. The study concludes that landlessness among the Santhal is a multidimensional issue requiring urgent, inclusive, and rights-based policy intervention.